Prevalence of hypothyroidism in first trimester screening and its association with maternal and foetal outcomes - R., Ashwini; Kandasamy, Vijayalakshmi; R., Sailatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Maternal hypothyroid is one of the common thyroid disorder. Hypothyroidism in pregnant women who are not treated can cause premature birth, low birth weight, and respiratory distress in the newborn. Objectives were to find out the prevalence of hypothyroidism in pregnant women during first trimester screening and its association with maternal and foetal outcomes. Methods: The present study was a hospital based study carried out in the department of obstetrics and gynaecology, Chettinad Hospital and Research Institute, Kelambakkam, Chennai, India between January 2021 and January 2023. The study was carried out among the pregnant women in the first trimester visiting the outpatient department of the OBG department during the study period. Based on the thyroid profile obtained, the participants were classified into normal, subclinical hypothyroidism and overt hypothyroidism. They were then followed up to record the maternal and foetal outcome. Results: A total of 2017 patients were included in the study. The prevalence of hypothyroidism was 15.3%. The distribution of type of delivery was found to be different between hypothyroid and normal groups with more number of women underwent Caesarean delivery (18.24%) in the hypothyroid group than those in normal group. The proportion of low birth weight was also statistically higher (45.28%) in the hypothyroid group than in the normal. Similar pattern was observed with birth asphyxia. The APGAR scores recorded were also significantly lower in the hypothyroid group than in the euthyroid group with p value of less than 0.05. Conclusions: The prevalence of hypothyroidism was 15.3%. In our study, women with hypothyroidism showed adverse maternal and foetal outcome such as more caesarean deliveries, low birth weight, and poor APGAR scores and were found to be statistically significant when compared to euthyroid women.